Kematian Dalam Prespektif Al-Quran - Ozi Setiadi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
This article aims to explain how death is in the perspective of the Koran. The background of this paper is that death is something that must happen and cannot be avoided. This happens to all living creatures, namely creatures that have a spirit in a (physical) body. The writing of the article uses a descriptive analysis method, where data from primary sources, namely the verses of the Koran that have been inventoried which are thought to be included in the theme of death, will be studied based on the interpretations of the commentators. This article concludes that Ibn Kathir, Sayyid Qutb, Buya Hamka, 'Aidh al-Qarni, and Quraish Shihab agree that death according to the Qur'an is something certain. However, no human can know when death will occur. Allah SWT. in the Qur'an only explains the existence of an agreement between humans and their rabb and the process of human creation, but does not explain when a creature will die. The Qur'an also explains about the reasons why a person will experience death, such as being killed, sick, and accidents. All of them become a person's way to death.